Genetic Engineering Antibody: Principles and Application. (October 2019) - Zhao, Lin; Wu, Qi; Song, Ruirui; Yun, Zhenyu
Abstract: Antibodies are proteins secreted by plasma cells of the immune system to bind antigens and trigger the immune effector activity. Genetic engineering antibodies are novel recombinant antibody molecules with improved antigen specificities and effector functions, which produced by the recombinant DNA and protein engineering technologies. The ability to produce antibodies that are directed against specific antigens drives scientific discovery and the development of clinical diagnosis and therapy. This paper provides an overview of the current studies on the principle, categories, generation and application of genetic engineering antibody.